Parieto-temporal pleomorphic xanthoastrocytoma in a black African child - Musara, Aaron (Asian J Neurosurg, 2017)
Pleomorphic xanthoastrocytoma (PXA) is a rare cerebral tumor, accounting for <1% of all astrocytic neoplasms. PXA, usually, has a favorable prognosis in spite of what might be suggested from the ominous microscopic appearance. There is no literature immediately available on the black population for this tumor. Management is by surgical resection. The ideal is gross total resection, which offers an excellent prognosis. This disease condition has not been reported in the black population. The following is a presentation of a case report in a black African girl, followed by a review of the literature.